Pengaruh Likuiditas, Ukuran Perusahaan dan Pergantian Auditor Terhadap Ketepatan Waktu Pelaporan Keuangan - Wahyu Dewi Retno Wulandari; Erni Yanti Natalia (Jurnal Ilmiah Wahana Pendidikan, 2023)
This study aims to determine the effect of liquidity, company size and auditor turnover on the timeliness of financial reporting in automotive sub-sector companies listed on the Indonesia Stock Exchange for the period 2017 to 2021. This study used an associative quantitative approach with a population of 13 companies and 9 companies were selected as samples. Using a purposive sampling technique in accordance with the research criteria. Secondary data in the form of financial reports are used in this study, for analysis and data processing using SPSS Version 26. The results of this study are that partially liquidity and also company size have a positive and significant effect on the timeliness of financial reporting where liquidity has a t count of 1.729 > 1 .6828 t table and company size has a t count value of 1.817 > 1.6828 t table. Meanwhile, auditor turnover is negative -0.047 and significance is 0.275 <0.05. Simultaneously liquidity, company size and auditor turnover affect the timeliness of financial reporting with a calculated F value of 2.680 > 2.45 F table.